THERMAL CONDITIONING USING PHASE CHANGE MATERIALS - Boucíguez, A.; Villa, L. T.; Lara, M. A. (Revista de Engenharia Térmica, 2003)
A combined procedure using a classical qualitative result for initial and boundary problems associated to parabolic equations, numerical treatment and computational simulation, have been used to obtain some results on the dynamic behavior of the function that provides the position of the melting interface or moving front of the phase change material at each time. This material is used in a special device that is designed in order to get thermal conditioning in physical - chemical systems of practical importance. A monotone dependence of the melting interface upon some parameters is also shown.